New record of the genus Brulleia Szépligeti, 1904 ( Hymenoptera: Braconidae: Helconinae ), with description of three new species from VietNam - Long, Khuat Dang; Hoa, Dang Thi; Nga, Cao Thi Quynh (Academia Journal of Biology, 2019)
The genus Brulleia Szépligeti, 1904 was recorded for the first time in Vietnam, three new species, namely Brulleia flavosoma Long, sp. n.; B. mellicrus  Long, sp. n. and B. nigrisoma Long, sp. n., were descripbed and illustrated. A key to Brulleia species from Vietnam is provided. The checklist of the already known species of the genus Brulleia is also given.